Teachers Solutions to English Teaching and Learning Problems at Senior High Schools, An Analysis of Teachers Classroom Action Research Reports - Ellis Tamela; Ratna Dewanti (Stairs, 2020)
This study was conducted to investigate the solutions to English teaching and learning problems at senior high schools in teachers classroom action research reports. The methodology of this study was a content analysis of the problems and solutions in teachers classroom action research reports. The data were the problems and teachers solutions in the English teaching and learning at senior high school in teachers classroom action research reports. The data sources were thirtyone reports of listening, speaking, reading, writing, and lexicogrammar. This study found that the teachers utilized various technique or method to solve the problems in four skills and lexicogrammar (such as, quartet cards, jigsaw, a series of pictures, etc.), even though they had similar problems. There were two solutions in listening problems, eleven solutions in speaking problems, eight solutions in reading problems, six solutions in writing problems, and one solution in lexicogrammar problem. Furthermore, there were reports which had different problems similar solutions (the use of quartet cards in speaking), and similar problems similar solutions (the use of jigsaw in reading and the use of series of pictures in writing).